Padrões de distribuição de líquidos obtidos com bicos TF-VS4, TJ60-11006 e TQ15006 em mesa de prova - Perecin, Dilermando [UNESP]; Peressin, Valdemir Antonio; Matuo, Tomomassa [UNESP]; Braz, Benedito Apparecido [UNESP]; Pio, Luís César (My University, 1998)
The performance of a spray boom can be evaluated from its individual nozzle distribution patterns determined in a patternator (test table), as discussed by Perecin et al. (1994). The distribution pattern of three nozzle types obtained in a patternator at six heights were compared in order to propose a formula for determining the variation coefficient. The simulation of a spray boom was conducted from individual nozzle distribution patterns, and obtained the random variation coefficients (RVC) and the systematic variation coefficients (SVC). The results showed good performance of the TF-SV4 nozzles, with CV smaller than 10%, for nozzle spacing as large as 50 cm. The TQ15006 nozzles showed high variability in the central region of the distribution pattern, resulting in high CV from nozzle spacings as narrow as 25 cm. The TJ60-11006 behaved as intermediate between TF-VS4 and TQ15006. The formula proposed for determining the variation coefficient is [(RVC) 2+(SVC) 2] 1/2.

A avaliação do desempenho de bicos de pulverização pode ser feita a partir do seu padrão de distribuição do líquido. Pelo método descrito em Perecin et al. (1994), analisaram-se comparativamente os padrões de deposição produzidos por bicos TF-VS4, TJ60-11006 e TQ15006 em mesa de prova, bem como as suas propriedades em barra total em termos dos coeficientes de variação sistemático (CVS), aleatório (CVA) e combinado (CVG), propondo-se uma fórmula para estimar o CVG da barra total. Os bicos TF-VS4 apresentaram CVG inferiores a 10%, mesmo com espaçamentos entre bicos de até 50 cm, e altura do alvo ao redor de 20 cm ou mais. Os bicos TQ15006 mostraram variabilidade acentuada na região central do padrão, o que proporcionou CVG em barra total superiores a 10%, com espaçamentos entre bicos maiores que 25 cm. Os bicos TJ60-11006 comportaram-se de forma intermediária entre os TF-VS4 e os TQ15006. A fórmula proposta para estimar o coeficiente de variação combinado é: CVG=[(CVA)2 + (CVS)2]1/2.
Distribution patterns of TF-VS4, TJ60-11006 and TQ15006 nozzles in a patternator
Keywords: Nozzle; Spray boom